An Extended Technology Acceptance of Wearable Devices for Ship-to-Shore (STS) Crane Operator in a Container Terminal - Setyonugroho, Winny; Utami, Sentagi Sesotya; Islami, Moch Zihad; Setiawan, Fandi; Handono, Janatarum Sri (Fakultas Seni Rupa dan Desain ITB, 2024)
This study aims to uncover factors that indicate employees' acceptability of wearable devices. The study utilizes the Technology Acceptance Model (TAM). It expands on Davis's framework by including six extra variables to gain thorough insights: social influence, technological anxiety, trust, perceived risk, perceived physical condition, and resistance to change. After the literature review, a close-ended questionnaire is created to implement the research. Fourty one Ship-to-Shore (STS) crane operators at PT Terminal Teluk Lamong participated in a five-month survey using wearable devices for work. The model's components are analyzed using exploratory and confirmatory factor analysis in a terminal crane operator environment. Structural equation modeling (SEM) is used to confirm the model. The research results show a strong connection between the independent and dependent variables, revealing the complex dynamics that impact the attitudes and intentions of high-risk workers. While other connections were not statistically significant, the study highlights the crucial influence of social characteristics on user attitudes toward technology adoption. This study expands TAM and provides practical guidance for introducing wearable devices to STS crane operators to improve technology acceptance in high-risk industries.